Strategi Pembelajaran Metode SAS untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas V Sekolah Dasar - Dian Kumaya Dewi; Suyatmi Suyatmi; Sawiyatun Sawiyatun (Universitas Muria Kudus, 2025)
Reading ability is a fundamental foundation for learning across subjects in elementary school. Preliminary observations in a public elementary school in Grobogan Regency revealed that some fifth-grade students still experienced difficulties recognizing word structures and understanding text meaning because reading instruction lacked systematic and staged strategies. This study aims to analyze the implementation of the Structural Analytic Synthetic (SAS) method to strengthen reading skills in upper elementary grades, extending SAS use beyond initial literacy learning. The research employed a qualitative descriptive design involving fifth-grade students as participants. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities and student work. Data analysis followed the stages of reduction, data display, and conclusion drawing to capture patterns of change during the learning process. The findings show that the SAS method improves students’ reading ability through three interconnected phases: structural (introducing meaningful word and sentence patterns), analytic (guiding students to break down structures and identify relationships among parts), and synthetic (supporting students to reconstruct meaning as a coherent whole). The learning process became more interactive, contextual, and motivating, helping students develop better reading fluency while also enhancing comprehension. These results indicate that SAS is an effective instructional alternative for reading development in higher-grade primary students and has practical implications for lesson design and teacher training focused on reading comprehension improvement.